Freefall - Gordon, Roderick; Williams, Brian James 1958- (New York : Chicken House, 2010)
As Will and his friends plummet down a subterranean pore, they face deadly creatures and discover a strange fungal shelf that reveals artifacts from ancient civilizations as well as clues to a lost land at the end of the Earth.
Originally published: Frome, Somerset, England : Chicken House, 2009.
Keywords: Archeology -- Fiction; London (England) -- Fiction; England -- Fiction; Adventure fiction